Shrinkage-resistant supercritical foaming shoe composite material and preparation method thereof

By using TPU resin, maleic anhydride graft modified olefin block copolymer and nano calcium carbonate/calcium phosphate composition in shoe composites, the problems of insufficient shrinkage resistance and poor dimensional stability of shoe composites are solved. It achieves both dimensional stability and anti-compression deformation performance, improving the user experience and service life.

CN119264648APending Publication Date: 2025-01-07FENGTE (FUJIAN) NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411590353.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The shoe composite materials on the market have problems of insufficient shrinkage resistance and poor dimensional stability, which leads to easy deformation during long-term storage, affecting the comfort and appearance of wearing.

Method used

Cell modification agents using 85-90 parts by weight of TPU resin, 10-15 parts by weight of maleic anhydride graft modified olefin block copolymer, and 1-2 parts by weight of nano calcium carbonate and calcium phosphate, provide anti-compression through TPU resin. Permanent deformation and wear resistance, combined with maleic anhydride graft modified olefin block copolymer to improve tear resistance and dimensional stability, and optimize cell structure through nano-calcium carbonate and calcium phosphate composition to improve compression resistance Deformation and tear resistance.

Benefits of technology

It achieves the dimensional stability and compression deformation resistance of shoe composite materials, reduces shrinkage rate, improves tear resistance, extends service life and improves user experience.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005125416180000121
    Figure BDA0005125416180000121
  • Figure BDA0005125416180000131
    Figure BDA0005125416180000131
  • Figure BDA0005125416180000132
    Figure BDA0005125416180000132
Patent Text Reader

Abstract

The invention discloses an anti-shrinkage supercritical foaming shoe material composite material and a preparation method thereof, and relates to the field of shoe materials. The anti-shrinkage supercritical foaming shoe composite material comprises 85-90 parts by weight of TPU resin, 10-15 parts by weight of a maleic anhydride grafted modified olefin block copolymer and 1-2 parts by weight of a cell modifier, the cell modifier comprises nano calcium carbonate and calcium phosphate, and the weight ratio of the nano calcium carbonate to the calcium phosphate is (3-4): 1. The anti-shrinkage supercritical foaming shoe material composite material has the advantage that the shrinkage rate is reduced, the size stability can be kept after long-time storage, meanwhile, the excellent compression permanent deformation resistance and tear resistance are achieved, the use experience of a user can be improved, and the service life of the supercritical foaming shoe material composite material is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of shoe materials, and in particular to an anti-shrinkage supercritical foaming shoe material composite material and a preparation method thereof. Background Art

[0002] At present, the composite materials for shoes on the market generally have problems such as insufficient anti-shrinkage performance and poor dimensional stability. They are prone to deformation during long-term storage, affecting wearing comfort and appearance.

[0003] In order to improve the dimensional stability of shoe material composite materials, related technologies usually add fillers to improve these problems. However, when the amount of filler added is small, the effect is not significant. When the amount of filler used is too large, the compression deformation resistance of the shoe material composite material will be significantly reduced. Therefore, it is urgent to provide a shoe material composite material that takes into account both dimensional stability and compression deformation resistance. Summary of the invention

[0004] In order to obtain a shoe material composite material that can achieve both dimensional stability and compression deformation resistance, the present application provides an anti-shrinkage supercritical foaming shoe material composite material and a preparation method thereof.

[0005] In the first aspect, the present application provides an anti-shrinkage supercritical foamed shoe material composite material adopts the following technical solution:

[0006] A shrinkage-resistant supercritical foaming shoe material composite material comprises 85-90 parts by weight of TPU resin, 10-15 parts by weight of maleic anhydride grafted modified olefin block copolymer and 1-2 parts by weight of a cell modifier, wherein the cell modifier comprises nano-calcium carbonate and calcium phosphate, and the weight ratio of the nano-calcium carbonate to the calcium phosphate is (3-4):1.

[0007] By adopting the above technical scheme, the TPU resin of the present application is used as the main material, and the TPU resin provides good compression permanent deformation performance and wear resistance. Maleic anhydride grafted modified olefin block copolymer is added to improve the tear resistance and dimensional stability of the shoe material composite material. At the same time, a composition with a specific ratio of nano calcium carbonate and calcium phosphate is used as a pore modifier, which not only optimizes the distribution uniformity of the pore structure and improves the compression deformation performance and tear resistance of the shoe material composite material, but also reduces the size of the pore structure and improves the dimensional stability of the shoe material composite material, so that the shoe material composite material has the advantage of reduced shrinkage rate, can maintain dimensional stability during long-term storage, and has excellent compression permanent deformation performance and tear resistance, which can improve the user experience and extend the service life of the supercritical foamed shoe material composite material.

[0008] In some specific embodiments, the raw materials for preparing the maleic anhydride grafted modified olefin block copolymer include maleic anhydride, olefin block copolymer and peroxidation initiator, and the weight ratio of maleic anhydride, olefin block copolymer and peroxidation initiator is (0.2-0.5):10:(0.01-0.02).

[0009] By adopting the above technical solution, maleic anhydride is grafted onto the olefin block copolymer, which is beneficial to enhancing the compatibility between the olefin block copolymer and the TPU resin, making the anti-shrinkage performance of the shoe material composite material more excellent, and is beneficial to further improving the dimensional stability of the shoe material composite material.

[0010] In some specific embodiments, the melt index of the olefin block copolymer is 4-6 g / 10 min, the test temperature of the melt index is 190° C., and the load is 2.16 kg.

[0011] By adopting the above technical solution, an olefin block copolymer with a melt index of 4-6g / 10min is used. The olefin block copolymer has good fluidity during processing, which is conducive to uniformly dispersing the maleic anhydride grafted modified olefin block copolymer into the TPU resin. In addition, the dimensional stability of the shoe material composite material can also be improved.

[0012] In some specific embodiments, the raw materials for preparing the TPU resin include polyether polyol, double-terminal alcohol hydroxyl long-chain alkyl silicone oil, 1,2-cyclohexanediamine, isocyanate component, catalyst and chain extender, and the weight ratio of the polyether polyol, double-terminal alcohol hydroxyl long-chain alkyl silicone oil, 1,2-cyclohexanediamine, isocyanate component, catalyst and chain extender is (45-50): (5.8-6.4): (2.5-3.0): (18-22): (0.1-0.15): (1-1.5).

[0013] By adopting the above technical scheme, the TPU resin is preferably a TPU resin prepared by reacting the polyether polyol, double-terminal hydroxyl long-chain alkyl silicone oil, 1,2-cyclohexanediamine, isocyanate component and chain extender in the above ratio. The synergistic effect of the polyether polyol, double-terminal hydroxyl long-chain alkyl silicone oil, 1,2-cyclohexanediamine, isocyanate component and chain extender significantly improves the shrinkage resistance of the TPU resin, thereby maintaining excellent dimensional stability of the shoe material composite material during storage, and at the same time, can further improve the tear resistance of the shoe material composite material.

[0014] In some specific embodiments, the molecular weight of the polyether polyol is 2000-3000.

[0015] By adopting the above technical solution, when the polyether polyol preferably has a molecular weight of 2000-3000, the resilience of the shoe material composite material is further improved, so that the shoe material composite material can quickly return to its original state after the external force is removed, thereby extending the service life of the shoe material composite material.

[0016] In some specific embodiments, the double-terminal alcohol hydroxyl long-chain alkyl silicone oil is double-terminal alcohol hydroxyl long-chain alkyl silicone oil IOTA-8865H.

[0017] By adopting the above technical solution, the double-terminal alcohol hydroxyl long-chain alkyl silicone oil IOTA-8865H is selected. The introduction of this silicone oil chain segment can significantly improve the dimensional stability of the TPU resin after foaming, thereby improving the uniformity and stability of the product.

[0018] In some specific embodiments, the isocyanate component is an alicyclic diisocyanate or an aromatic diisocyanate.

[0019] By adopting the above technical solution, the isocyanate component uses alicyclic diisocyanate or aromatic diisocyanate, which helps to improve the shrinkage resistance of TPU resin, so that the shoe material composite material maintains excellent dimensional stability during storage.

[0020] In some specific embodiments, the chain extender is at least one of ethylene glycol, 1,3-propylene glycol, and 1,4-butanediol.

[0021] In some specific embodiments, the method for preparing the TPU resin comprises the following steps:

[0022] After the polyether polyol is melted at 45-50° C., double-terminal alcohol hydroxyl long-chain alkyl silicone oil, 1,2-cyclohexanediamine and a catalyst are added, and mixed evenly to obtain a premix;

[0023] Add the isocyanate component to the premix, heat to 75-85° C. and react for 3.5-4.0 hours, then add the chain extender, continue to react at 75-85° C. for 1-2 hours, then cool and granulate to obtain TPU resin.

[0024] Through the synergistic effect of polyether polyols, double-terminal hydroxyl long-chain alkyl silicone oil, 1,2-cyclohexanediamine, isocyanate components, catalysts and chain extenders, a TPU resin with good shrinkage resistance can be obtained, so that the shoe material composite material maintains excellent dimensional stability during storage, and at the same time, the tear resistance of the shoe material composite material can be further improved.

[0025] In the second aspect, the present application provides a method for preparing a shrinkage-resistant supercritical foamed shoe material composite material using the following technical solution:

[0026] A method for preparing a shrinkage-resistant supercritical foaming shoe material composite material comprises the following steps:

[0027] S1, melting TPU resin, maleic anhydride grafted modified olefin block copolymer and cell modifier at 190-200° C., cooling and granulating to obtain modified TPU particles;

[0028] S2, putting the modified TPU particles into a reactor, heating it to 80-90° C. for preheating, and then introducing carbon dioxide gas into the reactor until the pressure in the reactor reaches 14-15 MPa;

[0029] S3, circulating the carbon dioxide gas in the reactor, maintaining the pressure in the reactor at 14-15 MPa during the circulation process, so that the modified TPU particles can be evenly contacted with the carbon dioxide gas;

[0030] S4. Continue to maintain the pressure of the reactor at 8-10MPa and the temperature at 30-40°C, and maintain the pressure and penetrate for 1-2h;

[0031] S5. Open the reactor to release the pressure, then put the modified TPU particles into a foaming device for foaming at a foaming temperature of 140° C.-150° C. for 1-2 min to obtain a shrinkage-resistant supercritical foamed shoe material composite material.

[0032] By adopting the above technical solution, the shoe material composite material provided by the present application can achieve the stability of the internal pore structure of the material, improve the shrinkage resistance of the shoe material composite material, and thus enable the shoe material composite material to maintain excellent dimensional stability during storage.

[0033] In summary, this application at least includes the following beneficial technical effects:

[0034] (1) The present application provides good compression set resistance and wear resistance through TPU resin, adds maleic anhydride grafted modified olefin block copolymer to improve the tear resistance and dimensional stability of the shoe material composite material, and uses a composition of nano calcium carbonate and calcium phosphate in a specific ratio as a cell modifier, which not only optimizes the distribution uniformity of the cell structure and improves the compression set resistance and tear resistance of the shoe material composite material, but also reduces the size of the cell structure and improves the dimensional stability of the shoe material composite material, so that the shoe material composite material has the advantage of reduced shrinkage rate and can maintain dimensional stability during long-term storage. At the same time, it has excellent compression set resistance and tear resistance, which can improve the user experience and extend the service life of the supercritical foamed shoe material composite material.

[0035] (2) In the present application, the TPU resin is preferably a TPU resin obtained by reacting the polyether polyol, double-terminal hydroxyl long-chain alkyl silicone oil, 1,2-cyclohexanediamine, isocyanate component and chain extender in the above-mentioned ratio. The synergistic effect of the polyether polyol, double-terminal hydroxyl long-chain alkyl silicone oil, 1,2-cyclohexanediamine, isocyanate component and chain extender significantly improves the shrinkage resistance of the TPU resin, thereby allowing the shoe material composite material to maintain excellent dimensional stability during storage. At the same time, it can also further improve the tear resistance of the shoe material composite material. DETAILED DESCRIPTION

[0036] The present application is further described below in conjunction with specific experiments.

[0037] Preparation Example

[0038] [Preparation Example 1]

[0039] A TPU resin comprises the following raw materials:

[0040] Polyether polyol: 45 kg; In this preparation example, the polyether polyol specifically uses polytetrahydrofuran ether diol with a molecular weight of 2000, and the polytetrahydrofuran ether diol is purchased from Jiangsu Haolong Chemical Co., Ltd.;

[0041] 1,2-cyclohexanediamine: 8.3kg;

[0042] Isocyanate component: 18 kg. In this preparation example, the isocyanate component is specifically isophorone diisocyanate;

[0043] Catalyst: 0.1 kg. In this preparation example, the catalyst is dibutyltin dilaurate;

[0044] Chain extender: 1 kg; in this preparation example, the chain extender specifically uses 1,3-propylene glycol.

[0045] In this preparation example, the preparation method of TPU resin includes the following steps:

[0046] After the polyether polyol is melted at 48° C., 1,2-cyclohexanediamine and a catalyst are added and mixed evenly to obtain a premix;

[0047] The isocyanate component was added to the premix, and the temperature was raised to 80°C for reaction for 3.8 hours. Then, the chain extender was added, and the reaction was continued at 80°C for 1.5 hours. Then, the mixture was cooled and granulated to obtain TPU resin.

[0048] [Preparation Example 2]

[0049] A TPU resin comprises the following raw materials:

[0050] Polyether polyol: 45 kg; In this preparation example, the polyether polyol specifically uses polytetrahydrofuran ether diol with a molecular weight of 2000, and the polytetrahydrofuran ether diol is purchased from Jiangsu Haolong Chemical Co., Ltd.;

[0051] Double-terminal alcohol hydroxyl long-chain alkyl silicone oil: 8.3 kg; in this preparation example, the double-terminal alcohol hydroxyl long-chain alkyl silicone oil specifically adopts the double-terminal alcohol hydroxyl long-chain alkyl silicone oil IOTA-8865H produced by Anhui Iyota Silicone Oil Co., Ltd.;

[0052] Isocyanate component: 18 kg. In this preparation example, the isocyanate component is specifically isophorone diisocyanate;

[0053] Catalyst: 0.1 kg. In this preparation example, the catalyst is dibutyltin dilaurate;

[0054] Chain extender: 1 kg; in this preparation example, the chain extender specifically uses 1,3-propylene glycol.

[0055] In this preparation example, the preparation method of TPU resin includes the following steps:

[0056] After the polyether polyol is melted at 48° C., a double-terminal alcohol hydroxyl long-chain alkyl silicone oil and a catalyst are added and mixed evenly to obtain a premix;

[0057] The isocyanate component was added to the premix, and the temperature was raised to 80°C for reaction for 3.8 hours. Then, the chain extender was added, and the reaction was continued at 80°C for 1.5 hours. Then, the mixture was cooled and granulated to obtain TPU resin.

[0058] [Preparation Example 3]

[0059] A TPU resin comprises the following raw materials:

[0060] Polyether polyol: 45 kg; In this preparation example, the polyether polyol specifically uses polytetrahydrofuran ether diol with a molecular weight of 2000, and the polytetrahydrofuran ether diol is purchased from Jiangsu Haolong Chemical Co., Ltd.;

[0061] Double-terminal alcohol hydroxyl long-chain alkyl silicone oil: 5.8 kg; in this preparation example, the double-terminal alcohol hydroxyl long-chain alkyl silicone oil specifically adopts the double-terminal alcohol hydroxyl long-chain alkyl silicone oil IOTA-8865H produced by Anhui Iyota Silicone Oil Co., Ltd.;

[0062] 1,2-cyclohexanediamine: 2.5kg;

[0063] Isocyanate component: 18 kg. In this preparation example, the isocyanate component is specifically isophorone diisocyanate;

[0064] Catalyst: 0.1 kg. In this preparation example, the catalyst is dibutyltin dilaurate;

[0065] Chain extender: 1 kg; in this preparation example, the chain extender specifically uses 1,3-propylene glycol.

[0066] In this preparation example, the preparation method of TPU resin includes the following steps:

[0067] After the polyether polyol is melted at 48° C., double-terminal alcohol hydroxy long-chain alkyl silicone oil, 1,2-cyclohexanediamine and a catalyst are added and mixed evenly to obtain a premix;

[0068] The isocyanate component was added to the premix, and the temperature was raised to 80°C for reaction for 3.8 hours. Then, the chain extender was added, and the reaction was continued at 80°C for 1.5 hours. Then, the mixture was cooled and granulated to obtain TPU resin.

[0069] [Preparation Example 4]

[0070] A TPU resin comprises the following raw materials:

[0071] Polyether polyol: 50 kg; in this preparation example, the polyether polyol specifically adopts polytetramethylene glycol with a molecular weight of 3000, and the polytetramethylene glycol is purchased from Jiangsu Haolong Chemical Co., Ltd.;

[0072] Double-terminal alcohol hydroxyl long-chain alkyl silicone oil: 6.4 kg; in this preparation example, the double-terminal alcohol hydroxyl long-chain alkyl silicone oil specifically adopts the double-terminal alcohol hydroxyl long-chain alkyl silicone oil IOTA-8865H produced by Anhui Iyota Silicone Oil Co., Ltd.;

[0073] 1,2-cyclohexanediamine: 3.0kg;

[0074] Isocyanate component: 22 kg. In this preparation example, the isocyanate component is specifically diphenylmethane diisocyanate;

[0075] Catalyst: 0.15 kg. In this preparation example, the catalyst is dibutyltin dilaurate;

[0076] Chain extender: 1.5 kg; in this preparation example, the chain extender is specifically 1,4-propylene glycol.

[0077] In this preparation example, the preparation method of TPU resin includes the following steps:

[0078] After the polyether polyol is melted at 48° C., double-terminal alcohol hydroxy long-chain alkyl silicone oil, 1,2-cyclohexanediamine and a catalyst are added and mixed evenly to obtain a premix;

[0079] The isocyanate component was added to the premix, and the temperature was raised to 80°C for reaction for 3.8 hours. Then, the chain extender was added, and the reaction was continued at 80°C for 1.5 hours. Then, the mixture was cooled and granulated to obtain TPU resin.

[0080] Example

[0081] [Example 1]

[0082] A shrinkage-resistant supercritical foaming shoe material composite material comprises the following raw materials:

[0083] TPU resin: 85 kg; in this embodiment, the TPU resin is the TPU resin prepared in [Preparation Example 1];

[0084] Maleic anhydride grafted modified olefin block copolymer: 10 kg; In this embodiment, the maleic anhydride grafted modified olefin block copolymer is obtained by melt grafting maleic anhydride, olefin block copolymer and benzoyl peroxide at a weight ratio of 0.2:10:0.01 at 175° C., wherein the olefin block copolymer is an olefin block copolymer of Dow brand 9500 in the United States;

[0085] Cell modifier: 1 kg; wherein the cell modifier is a combination of nano calcium carbonate and calcium phosphate, and the weight ratio of nano calcium carbonate to calcium phosphate is 4:1.

[0086] In this embodiment, the method for preparing the shrinkage-resistant supercritical foaming shoe material composite material comprises the following steps:

[0087] S1, melting TPU resin, maleic anhydride grafted modified olefin block copolymer and cell modifier at 190° C. in proportion, cooling and granulating to obtain modified TPU particles;

[0088] S2, put the modified TPU particles into the reactor, raise the temperature to 80°C for preheating, and then introduce carbon dioxide gas into the reactor until the pressure in the reactor reaches 14Mpa;

[0089] S3, circulating the carbon dioxide gas in the reactor, maintaining the pressure in the reactor at 14 MPa during the circulation process, so that the modified TPU particles can be evenly contacted with the carbon dioxide gas;

[0090] S4. Continue to maintain the pressure of the reactor at 10 MPa and the temperature at 30°C, and maintain the pressure and permeate for 1 hour;

[0091] S5. Open the reactor to release the pressure, then put the modified TPU particles into a foaming device for foaming at a foaming temperature of 140° C. for 2 min to obtain a shrinkage-resistant supercritical foamed shoe material composite material.

[0092] [Example 2]

[0093] A shrinkage-resistant supercritical foaming shoe material composite material comprises the following raw materials:

[0094] TPU resin: 90 kg; in this embodiment, the TPU resin is the TPU resin prepared in [Preparation Example 1];

[0095] Maleic anhydride grafted modified olefin block copolymer: 15 kg; In this embodiment, the maleic anhydride grafted modified olefin block copolymer is obtained by melt grafting maleic anhydride, olefin block copolymer and benzoyl peroxide at a weight ratio of 0.5:10:0.02 at 175° C., wherein the olefin block copolymer is an olefin block copolymer of Dow brand 9530 in the United States;

[0096] Cell modifier: 2kg; wherein the cell modifier is a combination of nano calcium carbonate and calcium phosphate, and the weight ratio of nano calcium carbonate to calcium phosphate is 3:1.

[0097] In this embodiment, the method for preparing the shrinkage-resistant supercritical foaming shoe material composite material comprises the following steps:

[0098] S1, melting TPU resin, maleic anhydride grafted modified olefin block copolymer and cell modifier at 200° C. in proportion, cooling and granulating to obtain modified TPU particles;

[0099] S2, put the modified TPU particles into the reactor, heat it to 90°C for preheating, and then introduce carbon dioxide gas into the reactor until the pressure in the reactor reaches 15Mpa;

[0100] S3, circulating the carbon dioxide gas in the reactor, maintaining the pressure in the reactor at 15 MPa during the circulation process, so that the modified TPU particles can be evenly contacted with the carbon dioxide gas;

[0101] S4, continue to maintain the pressure of the reactor at 8MPa and the temperature at 40°C, and maintain the pressure and penetrate for 2h;

[0102] S5. Open the reactor to release the pressure, then put the modified TPU particles into a foaming device for foaming at a foaming temperature of 150° C. for 1 min to obtain a shrinkage-resistant supercritical foamed shoe material composite material.

[0103] [Example 3]

[0104] A shrinkage-resistant supercritical foamed shoe material composite material, which is different from [Example 1] in that:

[0105] In this embodiment, the TPU resin is the TPU resin prepared in [Preparation Example 2].

[0106] [Example 4]

[0107] A shrinkage-resistant supercritical foamed shoe material composite material, which is different from [Example 1] in that:

[0108] In this embodiment, the TPU resin is the TPU resin prepared in [Preparation Example 3].

[0109] [Example 5]

[0110] A shrinkage-resistant supercritical foamed shoe material composite material, which is different from [Example 1] in that:

[0111] In this embodiment, the TPU resin is the TPU resin prepared in [Preparation Example 4].

[0112] Comparative Example

[0113] [Comparative Example 1]

[0114] A shrinkage-resistant supercritical foamed shoe material composite material, which is different from [Example 1] in that:

[0115] The maleic anhydride grafted modified olefin block copolymer is replaced by an equal amount of TPU resin obtained in [Preparation Example 1].

[0116] [Comparative Example 2]

[0117] A shrinkage-resistant supercritical foamed shoe material composite material, which differs from [Example 1] in that the calcium phosphate in the cell modifier is replaced by an equal amount of nano-calcium carbonate.

[0118] [Comparative Example 3]

[0119] A shrinkage-resistant supercritical foamed shoe material composite material, which differs from [Example 1] in that the nano calcium carbonate in the cell modifier is replaced by an equal amount of calcium phosphate.

[0120] Performance testing

[0121] (1) Compression set rate: The compression set performance of the supercritical foamed shoe material composite material was tested with reference to GB / T 6669-2008. The supercritical foamed shoe material composite material was injected into a mold cavity in the shape of a shoe sole, and the supercritical foamed shoe material composite material was subjected to steam molding. The supercritical foamed shoe material composite material was then cut into samples of 50 mm (length) × 50 mm (width) × 25 mm (thickness). The samples were compressed to 75% of the thickness, kept in an oven at 70° C. for 72 hours, and then released from compression. After the samples were taken out and allowed to recover for 30 minutes, the thickness of the samples was tested. Five samples were taken from each embodiment and comparative example for testing, and the average compression set rate of the five samples was calculated.

[0122] (2) Tear strength: The tear strength of the supercritical foamed shoe material composite material was tested with reference to HG 2726-1995. The supercritical foamed shoe material composite material was punched into a mold cavity in the shape of a shoe sole, and the supercritical foamed shoe material composite material was formed by steam molding. The supercritical foamed shoe material composite material was then cut into samples of 95 mm (length) × 25 mm (width) × 5 mm (thickness). The operating speed of the tensile testing machine was controlled to 100 mm / min. Five samples were tested for each embodiment and comparative example, and the average tear strength of the five samples was recorded.

[0123] (3) Dimensional shrinkage rate: The supercritical foamed shoe material composite material was injected into a mold cavity in the shape of a shoe sole, and the supercritical foamed shoe material composite material was formed by steam compression molding, and then cut into samples of 95 mm (length) × 25 mm (width) × 5 mm (thickness). Five samples of each embodiment and comparative example were heated in an oven at 35° C. for 72 h. The ratio of the reduced dimensions of the sample in the length direction and the width direction to the original dimensions was measured, which was the dimensional shrinkage rate. The average dimensional shrinkage rate of the five samples was recorded.

[0124] Table 1

[0125]

[0126]

[0127] Table 2

[0128]

[0129] The difference between Comparative Example 1 and Example 1 is that the maleic anhydride grafted modified olefin block copolymer in Comparative Example 1 is replaced by an equal amount of TPU resin obtained in [Preparation Example 1]. Combining the data in Tables 1-2, it can be seen that the compression permanent deformation rate and dimensional shrinkage rate of the supercritical foamed shoe material composite material in Comparative Example 1 increase, and the tear strength decreases, indicating that the addition of the maleic anhydride grafted modified olefin block copolymer can reduce the compression permanent deformation of the supercritical foamed shoe material composite material, and improve the dimensional stability and tear resistance of the supercritical foamed shoe material composite material.

[0130] The difference between Comparative Example 2-3 and Example 1 is that the calcium phosphate in the cell modifier in Comparative Example 2 is replaced by an equal amount of nano calcium carbonate, and the nano calcium carbonate in the cell modifier in Comparative Example 3 is replaced by an equal amount of calcium phosphate. Combining the data in Table 1-2, it can be seen that the compression permanent deformation rate and dimensional shrinkage rate of the supercritical foamed shoe material composite material in Comparative Example 2 and Comparative Example 3 increase, and the tear strength decreases, indicating that the cell modifier using a composite of the two can improve the compression permanent deformation of the supercritical foamed shoe material composite material, and improve the dimensional stability and tear resistance of the supercritical foamed shoe material composite material.

[0131] The difference between Example 4 and Examples 1 and 3 is that the TPU resin used in the supercritical foaming shoe material composite material in Example 4 is obtained by reacting a polyether polyol, a double-terminal alcohol hydroxyl long-chain alkyl silicone oil, 1,2-cyclohexanediamine, an isocyanate component and a chain extender, the TPU resin used in the supercritical foaming shoe material composite material in Example 1 is obtained by reacting a polyether polyol, 1,2-cyclohexanediamine, an isocyanate component and a chain extender, and the TPU resin used in the supercritical foaming shoe material composite material in Example 3 is obtained by reacting a polyether polyol, a double-terminal alcohol hydroxyl long-chain alkyl silicone oil, an isocyanate component and a chain extender. Combined with the data in Table 1-2, it can be seen that the compression permanent deformation rate and dimensional shrinkage rate of the supercritical foamed shoe material composite material in Example 4 are further reduced compared with Examples 1 and 3, and the tear strength is further improved compared with Examples 1 and 3, indicating that the TPU resin in the supercritical foamed shoe material composite material adopts the TPU resin obtained by reacting polyether polyol, double-end alcohol hydroxyl long-chain alkyl silicone oil, 1,2-cyclohexanediamine, isocyanate component and chain extender, which can further improve the compression deformation resistance, shrinkage resistance and tear resistance of the supercritical foamed shoe material composite material, improve the user experience, and extend the service life of the supercritical foamed shoe material composite material.

[0132] This specific implementation manner is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make non-creative modifications to the specific implementation manner as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A shrinkage-resistant supercritical foaming shoe material composite material, characterized in that: The invention comprises 85-90 parts by weight of TPU resin, 10-15 parts by weight of maleic anhydride grafted modified olefin block copolymer and 1-2 parts by weight of cell modifier, wherein the cell modifier comprises nano calcium carbonate and calcium phosphate, and the weight ratio of the nano calcium carbonate to the calcium phosphate is (3-4):

1.

2. The anti-shrinkage supercritical foaming shoe material composite material according to claim 1, characterized in that: The raw materials for preparing the maleic anhydride grafted modified olefin block copolymer include maleic anhydride, olefin block copolymer and peroxidation initiator, and the weight ratio of the maleic anhydride, olefin block copolymer and peroxidation initiator is (0.2-0.5): 10:(0.01-0.02)。 3. The anti-shrinkage supercritical foaming shoe material composite material according to claim 2, characterized in that: The melt index of the olefin block copolymer is 4-6 g / 10 min, the test temperature of the melt index is 190° C., and the load is 2.16 kg.

4. The shrinkage-resistant supercritical foaming shoe material composite material according to any one of claims 1 to 3, characterized in that: The raw materials for preparing the TPU resin include polyether polyol, double-terminal alcohol hydroxyl long-chain alkyl silicone oil, 1,2-cyclohexanediamine, isocyanate component, catalyst and chain extender, and the weight ratio of the polyether polyol, double-terminal alcohol hydroxyl long-chain alkyl silicone oil, 1,2-cyclohexanediamine, isocyanate component, catalyst and chain extender is (45-50): (5.8-6.4): (2.5-3.0): (18-22): (0.1-0.15): (1-1.5).

5. The anti-shrinkage supercritical foaming shoe material composite material according to claim 4, characterized in that: The molecular weight of the polyether polyol is 2000-3000.

6. The anti-shrinkage supercritical foaming shoe material composite material according to claim 4, characterized in that: The double-terminal alcohol hydroxyl long-chain alkyl silicone oil adopts double-terminal alcohol hydroxyl long-chain alkyl silicone oil IOTA-8865H.

7. The anti-shrinkage supercritical foaming shoe material composite material according to claim 4, characterized in that: The isocyanate component is alicyclic diisocyanate or aromatic diisocyanate.

8. The anti-shrinkage supercritical foaming shoe material composite material according to claim 4, characterized in that: The chain extender is at least one of ethylene glycol, 1,3-propylene glycol and 1,4-butanediol.

9. The anti-shrinkage supercritical foaming shoe material composite material according to claim 4, characterized in that: The preparation method of the TPU resin comprises the following steps: After the polyether polyol is melted at 45-50° C., double-terminal alcohol hydroxyl long-chain alkyl silicone oil, 1,2-cyclohexanediamine and a catalyst are added, and mixed evenly to obtain a premix; Add the isocyanate component to the premix, heat to 75-85° C. and react for 3.5-4.0 hours, then add the chain extender, continue to react at 75-85° C. for 1-2 hours, then cool and granulate to obtain TPU resin.

10. A method for preparing the shrinkage-resistant supercritical foamed shoe material composite material according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1, melting TPU resin, maleic anhydride grafted modified olefin block copolymer and cell modifier at 190-200° C. in proportion, cooling and granulating to obtain modified TPU particles; S2, putting the modified TPU particles into a reactor, heating it to 80-90° C. for preheating, and then introducing carbon dioxide gas into the reactor until the pressure in the reactor reaches 14-15 MPa; S3, circulating the carbon dioxide gas in the reactor, maintaining the pressure in the reactor at 14-15 MPa during the circulation process, so that the modified TPU particles can be evenly contacted with the carbon dioxide gas; S4. Continue to maintain the pressure of the reactor at 8-10MPa and the temperature at 30-40°C, and maintain the pressure and penetrate for 1-2h; S5. Open the reactor to release the pressure, then put the modified TPU particles into a foaming device for foaming at a foaming temperature of 140° C.-150° C. for 1-2 min to obtain a shrinkage-resistant supercritical foamed shoe material composite material.